(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concepts of upper and lower c-quasi (τ_1,τ_2)-continuous multifunctions. Moerover, several characterizations of upper and lower c-quasi (τ_1,τ_2)-continuous multifunctions are established.